Assessing the Impact of Poshan Abhiyan in Housing Colony Ompora: A Study on Local Participation, Government Efforts, and the Path to Enhanced Nutritional Outcomes - Tasleema Akhter (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Malnutrition remains a critical public health challenge in India, particularly among children under six years of age, pregnant women, and lactating mothers. To combat this issue, the Government of India launched Poshan Abhiyan, a comprehensive nutrition program aimed at eradicating malnutrition through multi-sectoral interventions, behavioral change communication, and improved service delivery. This study evaluates the implementation, challenges, and effectiveness of Poshan Abhiyan in Housing Colony Ompora, Budgam, Jammu & Kashmir, with a special focus on community participation and interdepartmental coordination. A mixed-method approach was used, incorporating primary data from surveys, interviews, and focus group discussions with Anganwadi worker, local beneficiaries, and health officials, alongside secondary data from official reports and government records. The findings indicate that while 62% of respondents were aware of Poshan Abhiyan, only 15% regularly accessed Anganwadi services, highlighting gaps in engagement. Additionally, 5% of children exhibited some degree of malnutrition, emphasizing the need for improved nutritional interventions and monitoring. The study also identifies challenges such as limited community awareness, inadequate interdepartmental coordination, and logistical issues in nutritional supplement distribution. To enhance program effectiveness, recommendations include strengthening awareness campaigns, fostering local participation, ensuring timely service delivery, and improving digital monitoring tools. This research underscores the importance of a collaborative approach involving local communities, government departments, and health workers to ensure the successful implementation of Poshan Abhiyan. Strengthening these efforts will play a pivotal role in achieving the long-term goal of a malnutrition-free India.